Future Engineer-Teachers’ Training for Using Information-Communicational Technologies - Horbatiuk, Roman (Pedagogical Discourse, 2012)
Future engineer-teachers’ training for using information-communicational technologies is groundeded in the article. The model for correction the general and vocational-oriented subjects’ study programs is worked out for different forms of study activities taking into account their professional aspect. The didactic conditions of students’ preparation are determined.